Characteristics of Misinformation in Social Networks. Comparative Study of the Hoaxs Denied in Argentina and Spain during 2020 - Gamir-Ríos, José (2022)
This paper studies the main features of fake news that circulated on social networks in Argentina and Spain during 2020, as well as their similarities and differences. The study carries out a content analysis of seven variables in 402 hoaxes that were debunked in both countries by the fact-checking platforms Chequeado and Newtral. Specifically, this article examines the sources of disinformation and their typologies, their main characters and their attributes, thematic affiliation, the emotions they appeal to, and the populist traits they represent. The results show the predominance of (a) anonymous sources in both countries, real media sources in Argentina and impersonated political entities in Spain; (b) deception as a form of disinformation; (c) the focus on the political class, almost always associated with negative attributes; (d) health as the central theme, an aspect derived from the COVID-19 pandemic, followed by the quality of democracy in Argentina and by consumption and personal political issues in Spain; (e) the appeal to negative emotions, especially anger and fear, both typical of negative affective polarization; and (f) the attack on elites and the defense of citizens’ interests as populist discursive features.